Shovel-truck systems : modelling, analysis and calculations - Czaplicki, Jacek M. (CRC Press/Balkema, 2009)
Presents a comprehensive analysis of the exploitation process of shovel-truck systems using modeling, analysis and calculations. This book discusses the functioning of a truck-repair shop system. It is suitable for mining engineers and civil engineers involved in use and development of shovel-truck systems, technology and planning.